Interactive Effect of Gender, Type of School and Mental Health on Social Adjustment of Adolescents - Verma, Kavita (INDIAN EDUCATIONAL REVIEW, 2015)
This research examined the interactive effect of gender, type of school and mental health on social adjustment of higher secondary school students of Chhattisgarh. Adjustment inventory by Sinha and Singh (2009) and Mental Health Battery by Singh and Sengupta (2008) were administrated on a sample of 480 higher secondary school students selected through disproportionate stratified random sampling technique from various government and private school of four districts of Chhattisgarh state, namely Durg, Raipur, Balod and Rajnandgoan. Data were analysed using 2×2 ×2 factorial design. Results revealed that gender, type of school and mentalhealth do not influence the social adjustment of the students. It was further found that the main effect of gender was not significant whereas the main effects of type of school and mental health were significant. However, none of the interaction effects were found to be significant. The result has been explained in terms of the factors influencing social adjustment of adolescents. The study will pave way for implementing intervention programmes on mental health for improving social adjustment of adolescents, modification in teaching learning process and curriculum modification.